Design and Control of Swarm Dynamics - Bouffanais, Roland; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
The book is about the key elements required for designing, building and controlling effective artificial swarms comprised of multiple moving physical agents. Therefore this book presents the fundamentals of each of those key elements in the particular frame of dynamic swarming, specifically exposing the profound connections between these elements and establish some general design principles for swarming behaviors. This scientific endeavor requires an inter-disciplinary approach: biomimetic inspiration from ethology and ecology, study of social information flow, analysis of temporal and adaptive signaling network of interaction, considerations of control of networked real-time systems, and lastly, elements of complex adaptive dynamical systems. This book offers a completely new perspective on the scientific understanding of dynamic collective behaviors thanks to its multi-disciplinary approach and its focus on artificial swarm of physical agents. Two of the key problems in understanding the emergence of swarm intelligent behaviors are identifying the social interaction rules a.k.a. the behavioral algorithm and uncovering how information flows between swarming agents. While most books about swarm dynamics have been focusing on the former, this book emphasizes the much-less discussed topic of distributed information flow, always with the aim of establishing general design principles.
Complexity and swarming systems -- A biologically-inspired approach to collective behaviors -- A physical approach to swarming -- A network-theoretic approach to collective dynamics -- An information-theoretic approach to collective behaviors -- A computational approach to collective behaviors -- Outlook: Can swarms be designed?.
Keywords: Dynamics; Nonlinear theories; System theory; Control engineering; Mathematical physics; Applied Dynamical Systems; Complex Systems; Control and Systems Theory; Theoretical, Mathematical and Computational Physics